Kirschner wire fixation of Salter-Harris type IV fracture of the lateral aspect of the humeral condyle in growing dogs - Cinti, Filippo; Pisani, Guido; Vezzoni, Luca; Peirone, Bruno; Vezzoni, Aldo (Veterinary and Comparative Orthopaedics and Traumatology, 2017)
Objectives: To evaluate the use of Kirschner wires for treatment of fractures of the lateral aspect of the humeral condyle in growing dogs.Methods: Retrospective analysis of 35 elbow fractures (33 dogs) of the lateral aspect of the humeral condyle treated by insertion of multiple transcondylar and one anti-rotational Kirschner wires. Radiographic and clinical re-evaluations were carried out immediately after surgery, at four weeks and, when required, at eight weeks postoperatively. Long-term follow-up was planned after a minimum of six months. The relationship between different implant configurations and clinical outcome was analysed statistically.Results: Complete functional recovery was seen in 31 elbows (30 dogs), three elbows (2 dogs) had reduction in the range of motion, and one elbow (1 dog) had persistent grade 1 lameness two months postoperatively. Major complications occurred in eight elbows (8 dogs) and all were resolved by implant removal. Implant configuration did not affect outcome. Long-term evaluation in 12 cases with a mean follow-up of four years showed absence of lameness, normal function and no or mild radiographic evidence of osteoarthritis in 11 cases.Clinical significance: Fracture of the lateral aspect of the humeral condyle in growing dogs can be successfully treated by multiple transcondylar convergent or parallel Kirschner wires, resulting in adequate fracture healing.
Keywords: Immature dogs; fracture of humeral condyle; Kirschner wire